Cell-Permeable Microprotein from Panax Ginseng Protects Against Doxorubicin-Induced Oxidative Stress and Cardiotoxicity - Bamaprasad Dutta; Shining Loo; Antony Kam; Xiaoliang Wang; Na Wei; Kathy Qian Luo; Chuan-Fa Liu; James P. Tam (Antioxidants)
(1) Background: Doxorubicin (DOX) is a frontline chemotherapeutic, but its side-effects from oxidative stress, leading to cardiotoxicity, pose significant challenges to its clinical use. We recently discovered a novel family of proteolysis-resistant, cystine-dense, and cell-penetrating microproteins from Panax ginseng that we term ginsentides. Ginsentides, such as the 31-residue TP1, coordinate multiple biological systems to prevent vascular dysfunction and endoplasmic reticulum stress induced by internal and external stressors. (2) Methods: We assessed the protective effects of ginsentide TP1 on DOX-induced cardiotoxicity using both in vitro functional studies on H9c2 cardiomyocytes and in vivo animal models by zebrafish and ICR mouse models. In these models, we examined oxidative stress, apoptosis, intracellular calcium levels, mitochondrial function, inflammatory responses, and cardiac function. (3) Results: We show that ginsentide TP1 protects against DOX-induced cytotoxicity in the mitochondria-rich H9c2 cardiomyocytes and reduces myocardial injury in zebrafish and mice by mitigating oxidative stress, inflammation, calcium, and mitochondrial dysfunction, as well as apoptosis-mediated cell death. Importantly, TP1 preserves cellular homeostasis without compromising the anticancer potency of DOX in breast cancer cells. (4) Conclusions: our findings highlight a specific antioxidative function of ginsentide TP1 in managing DOX-induced cardiotoxicity during cancer treatment and provide a promising lead for developing cardioprotective peptides and microproteins against oxidative stress.